A COMPARATIVE STUDY ON PHYSICAL AND MENTAL HEALTH DIFFERENCES BETWEEN PREGNANT AND NON-PREGNANT WOMEN: INSIGHTS FROM A CROSS-SECTIONAL ANALYSIS (The Research of Medical Science Review, 2025)
BackgroundPregnancy induces significant physiological and psychological changes, often leading to elevated stress, anxiety, and depression. This study aimed to compare physical and mental health parameters between pregnant and non-pregnant women to identify disparities and guide targeted interventions.MethodsA cross-sectional study was conducted on 200 participants (100 pregnant, 100 non-pregnant) recruited from a healthcare institution in Hyderabad, Pakistan. Physical health parameters, including BMI, blood pressure, and waist-hip ratio, were measured. Mental health was assessed using validated scales for stress, anxiety, and depression. Data were analyzed using descriptive statistics, independent t-tests, and correlation analyses.ResultsPregnant women exhibited higher BMI (29.5 ± 3.0 vs. 23.8 ± 2.5, p < 0.0001), systolic blood pressure (125 ± 7.5 mmHg vs. 115 ± 7.0 mmHg, p < 0.0001), and waist-hip ratio (0.95 ± 0.07 vs. 0.82 ± 0.06, p < 0.0001) compared to non-pregnant women. Mental health scores were also significantly elevated in the pregnant group, with stress (3.5 ± 0.8 vs. 1.5 ± 0.6, p < 0.0001), anxiety (3.4 ± 0.9 vs. 1.4 ± 0.5, p < 0.0001), and depression (3.3 ± 0.9 vs. 1.3 ± 0.6, p < 0.0001). Correlations were observed between BMI and blood pressure (r = 0.76, p < 0.0001) and between stress, anxiety, and depression (r > 0.80, p < 0.0001).ConclusionPregnant women exhibited significantly higher BMI, blood pressure, and mental health distress compared to non-pregnant women. The findings highlight the need for integrating routine mental health screenings and targeted interventions in antenatal care. Future longitudinal research should explore the persistence of these disparities postpartum.